2014
DOI: 10.1186/1471-2431-14-223
|View full text |Cite
|
Sign up to set email alerts
|

Association between parent-infant interactions in infancy and disruptive behaviour disorders at age seven: a nested, case–control ALSPAC study

Abstract: BackgroundEffective early intervention to prevent oppositional/conduct disorders requires early identification of children at risk. Patterns of parent-child interaction may predict oppositional/conduct disorders but large community-based prospective studies are needed to evaluate this possibility.MethodsWe sought to examine whether the Mellow Parenting Observational System (MPOS) used to assess parent-infant interactions at one year was associated with psychopathology at age 7. The MPOS assesses positive and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…We suggest that this has important implications for developing Mellow Parenting in routine practice. Mellow Parenting and other programmes involving parents and young children would benefit from a clear, standardized set of outcome measures focussed on tracking pre–post change in maternal (parental) mental health, indicators of child social, emotional, and linguistic development, and perhaps parent–infant interaction . As Mellow Parenting training is delivered through an international network of trainers, there is scope for developing a routine framework for this intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We suggest that this has important implications for developing Mellow Parenting in routine practice. Mellow Parenting and other programmes involving parents and young children would benefit from a clear, standardized set of outcome measures focussed on tracking pre–post change in maternal (parental) mental health, indicators of child social, emotional, and linguistic development, and perhaps parent–infant interaction . As Mellow Parenting training is delivered through an international network of trainers, there is scope for developing a routine framework for this intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Mellow Parenting and other programmes involving parents and young children would benefit from a clear, standardized set of outcome measures focussed on tracking pre-post change in maternal (parental) mental health, indicators of child social, emotional, and linguistic development, [37][38][39][40] and perhaps parent-infant interaction. 11 As Mellow Parenting training is delivered through an international network of trainers, there is scope for developing a routine framework for this intervention. A parallel example from clinical interventions in adult mental health is the increasing use of standardized outcomes in mentalization-based therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The longer the duration of breastfeeding, the increased protection against breast and ovarian cancer, and reduced post-menopausal hip fractures [ 23 , 24 , 25 , 26 , 27 ]. Emerging evidence suggests that breastfeeding positively impacts mother-baby relationships, bonding, and post-natal depression [ 28 , 29 , 30 ]. From an economic perspective, the improvements in child and maternal morbidity and mortality, plus reduced workforce productivity loss are estimated to be substantial [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 Longitudinal studies from many countries show that positive, consistent and supportive parenting predicts low levels of child problem behaviour and child abuse, and also predicts enhanced cognitive development. [6][7][8][9][10][11][12] Conversely, harsh inconsistent parenting predicts a broad range of poor child outcomes. 6,[13][14][15][16] Several studies have shown that increased levels of depressive symptoms in the parent are associated with less sensitive and harsher parenting behaviours.…”
Section: Maternal Depressionmentioning
confidence: 99%